The importance of the Kanchalan River, Chukotka, Russia, for the Lesser White-fronted Goose Anser erythropus - Heinicke, Thomas; Yakushev, Nikolay N; Syroechkovski, Jr, Evgeny E (Wildfowl, 2013)
An expedition was made to two different parts of the Anadyr region, southern Chukotka in summer 2006, to make an inventory of the bird fauna of the region. The Lesser White-fronted Goose Anser erythropus was found for the first time in both areas. Significant numbers ( 1% of the eastern flyway population of the species) were counted in the middle reaches of the Kanchalan River in mid-June, with smaller numbers seen on moult migration in the coastal region of Russkaya Koshka during early July. Total numbers in the Kanchalan floodplain were estimated at 150–200 birds, of which 40–50 were paired adults and the rest non-breeders. These numbers indicate that the area is of international importance for the species. Although breeding was not recorded, the birds’ location and habitat structure make the breeding of the species in the area likely.